The problem of integrated research of the subject of tolerance - I A Novikova; T I Ibadova (Peoples' Friendship University of Russia (RUDN University), 2009)
The article deals with the topical issues of studying of the problem of tolerance. The authors analyze the results of empirical studies of tolerance to the different levels of functioning of the individual.